Shape optimization, homogenization and optimal control : DFG-AIMS workshop held at the AIMS Center Senegal, March 13-16, 2017 /: DFG-AIMS workshop held at the AIMS Center Senegal, March 13-16, 2017. (2018) - Unknown
No abstract available